Optimization of Materials Research and Development Function in Creating Defense Equipment Which Modern and Adaptive to Support the Main Tasks of the TNI AD - Wahyudi, Indra; Pujiati, Herni (Dinasti Publisher, 2025)
Research and Development of the Indonesian Army (TNI AD) is one of the special functions in the TNI AD which is inherent in every TNI AD unit and it has a very important role in realizing the modernization of the TNI AD both in terms of personnel, systems, methods and materials. In accordance with this function, every year the ranks of the R&D Center Executive Agency and Main Command carry out R&D activity programs, both Material, personnel, Systems and Methode, which begin with the preparation and submission of R&D proposals. To ensure the optimization of R&D activities, especially material R&D, it is necessary to improve the quality of Human Resources (HR), facilities and infrastructure, and adequate budget support. Human Resources (HR) is one of the important elements for organizational operations in producing quality innovations and R&D products in accordance with the needs of user units, the existence of facilities and infrastructure as the main support for the implementation of a material R&D as well as activity process. Good quality of facilities and infrastructure will produce precise and accurate R&D products as expected. The success in the implementation of materials R&D will certainly not be separated from adequate budget support. The material R&D process requires considerable budget support before becoming an R&D product that is ready for mass production.